Analysis of quality implementation and supervision of vocational high schools using a qualitative approach - Elfi Tasrif; Mussa Saidi Abubakari; Hendra Hidayat (Jurnal Pendidikan Vokasi, 2022)
Academic supervision makes vocational high schools able to improve the quality of graduates to be ready to work and able to compete in the job market in people's lives. This paper aims to explore and describe the implementation of quality and supervision of vocational high schools using a qualitative approach. This type of qualitative research with a case study research design. The main target of this research is the supervisor of a vocational school in the city of Padang. This study is limited to a qualitative description of the implementation of quality and supervision of Vocational High Schools. The source of this research data is from key-informant, purposively. Data collection techniques with interview and observation techniques. Analyze data by coding, linking, and interpreting themes. The results of the research are: 1.) Supervisors are not ready to carry out supervision; 2.) The education office is less than optimal in empowering supervisors; 3.) Supervisors are less aggressive in positioning themselves; 4.) The coordinator of supervisors does not carry out his functions optimally; 5.) The low motivation of supervisors; 6.) The distribution of procurement of supervisors is uneven; 7.) The control mechanism for supervisors and the coordinator of supervisors is not working properly; 8.) Reward and punishment do not work; 9.) School visits are just routine; and 10.) Relations with teachers and schools are not well established. The conclusion is that the implementation of academic supervision is still not running optimal and lacks good communication and coordination.